Pengaruh Kartu Jakarta Pintar dan Project Based Learning terhadap Pengembangan Akademik Siswa SMK YMIK Joglo - siti rubiyati (CV. Kalimasada Group, 2025)
This study examines the influence of the provision of the Jakarta Smart Card and the implementation of project-based learning methods on the academic development of students at SMK YMIK Joglo. The background to this is based on the results of observations that show low academic achievement of students, which is characterized by a lack of independence in learning, absence from class in learning and lack of skills in working on projects. The scope of the discussion is focused on identifying the partial and simultaneous influence of the Jakarta Smart Card and project-based learning on academic development. This study uses a quantitative approach by collecting questionnaire data distributed to 109 students. Multiple linear regression analysis was carried out with the help of SPSS version 25. The results showed that the Jakarta Smart Card had a significant positive influence on students' academic development, namely 42.4%, while project-based learning also showed positive and significant results with a contribution of 41.5%. Simultaneously, the contribution of both was 52.9%. These findings confirm that the Jakarta Smart Card and project-based learning play an important role in improving students' academic achievement.